Decomposition of triangles into isosceles triangles I: let the students ask bravely - Kosztolányi, József; Kovács, Zoltán; Nagy, Erzsébet (Teaching Mathematics and Computer Science, 2004)
We report about working up an open geometric problem as a mathematical research with pupils of a mathematics camp. This paper shows the didactic aims and the methods we worked with, the didactic results. The second part of this paper gives a general solution of the problem, using pure mathematics and a computer programme.